2015
DOI: 10.1182/blood.v126.23.268.268
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival (OS) of Acute Lymphoblastic Leukemia (ALL) Is Better When Initial Therapy Is Administered in Academic Hospitals (AH) Versus Non-Academic Hospitals (NAH): A Retrospective Analysis of the National Cancer Data Base (NCDB)

Abstract: Introduction During initial diagnosis and therapy, patients with ALL can develop life-threatening complications such as sepsis, leukostasis, hemorrhage, and tumor lysis syndrome. Dedicated multidisciplinary leukemia teams may be needed to provide optimal management of such complications and selection of optimal therapeutic strategy. AH are more likely to have such expertise, adequate resources, standard operating policies and clinical trials, which may influence early mortality and OS. Such tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Private insurance coverage has been associated with improved health outcomes for patients with cancer (compared with public insurance), 1,3 and has been shown to be associated with an increased likelihood of receiving treatment at an SCC, which may improve outcomes in this patient population. 31,32 Although the ACA-DCE was predicted to improve coverage and therefore access in the young adult population, it did so for a subset of patients traditionally associated with access to resources and health care. However, young adults have been shown to have difficulty obtaining care even with insurance because of high outof-pocket costs; therefore, insurance coverage does not directly translate into increased access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Private insurance coverage has been associated with improved health outcomes for patients with cancer (compared with public insurance), 1,3 and has been shown to be associated with an increased likelihood of receiving treatment at an SCC, which may improve outcomes in this patient population. 31,32 Although the ACA-DCE was predicted to improve coverage and therefore access in the young adult population, it did so for a subset of patients traditionally associated with access to resources and health care. However, young adults have been shown to have difficulty obtaining care even with insurance because of high outof-pocket costs; therefore, insurance coverage does not directly translate into increased access.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study carry important consequences for health outcomes. Private insurance coverage has been associated with improved health outcomes for patients with cancer (compared with public insurance), and has been shown to be associated with an increased likelihood of receiving treatment at an SCC, which may improve outcomes in this patient population . Although the ACA‐DCE was predicted to improve coverage and therefore access in the young adult population, it did so for a subset of patients traditionally associated with access to resources and health care.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, it has demonstrated comorbidities are important prognostic variables in multiple different cancers [17][18][19][20]. It has been shown in previous studies that the treatment facility affects survival outcomes for many different cancers [10][11][12][13]. This topic has never been studied in SRCCE or in any subtype of esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of increased disease-specific mortalities for SRCCE include being unmarried, tumor size > 5 cm, higher tumor grade, invasion of adjacent organs, regional lymph node metastasis, distant metastasis, and no chemotherapy [9]. Previous studies have shown a strong correlation between type of treatment facility and survival for different cancers, but the effect of treatment facility on survival has not been studied in SRCCE [10][11][12][13]. The goal for this study is to assess any difference in survival based on treatment facility type and race.…”
Section: Introductionmentioning
confidence: 99%